Historical development of the expert status in Armenia - Chakhoyan, Artur (Bulletin of Yerevan University C: Jurisprudence, 2024)
The article examines the genealogy of the expert and his status, historical development from the Middle Ages to the present day, given that at all times experts have played an important role in the process of preventing, uncovering and investigating crimes, with the assistance of which the body carrying out the proceedings was able to obtain evidence, disclose circumstances relevant to the case.For this purpose, the judicial books of Mkhitar Gosh and Smbat Sparapet, the "canonical legislation" of David Alavka's son, the "Judicial Book of the Armenians of Astrakhan" created by Egiazar Grigoryan, Grigor Kanpanyan and Hovhannes' son Sarkis, the "trap of Glory" by Shaamir Shaamiryan were studied.The article also studied, analyzed and summarized the provisions provided for by the Criminal Procedure Code of the Armenian SSR, adopted on March 7, 1961, and the Criminal Procedure Code of the Republic of Armenia, adopted on July 1, 1998, concerning the status of an expert, the legal positions of the Court of Cassation of the Republic of Armenia regarding the main objectives of the specialist and expert.As a result of studying the legal monuments of Armenia, it is confirmed that even in the Middle Ages, the courts assigned a large role in investigating crimes to experts - "experienced", "knowledgeable" persons and the knowledge they applied.
Keywords: Science; technology; expert; experienced; knowledgeable; specialist; status; book of judgments; special knowledge; abilities